The Mediation Effect of Strategic Leadership in the Relationship between Knowledge Management, Competitive Intelligence and Business Strategy Formulation - Noor, Dr. Norzanah Mat; Nordin, Dr. Rumaizah Mohd; Rahim, Dr. Siti Sakinah Ab.; Shaikh, Dr. Mohsin (The journal of contemporary issues in business and government, 2021)
Business Strategy Formulation (BSF) from various diverse approach have been addressed in a number of previous researches that provided some distinct answers. However, the key to competitiveness is no longer based on the adoption of approach that have been successful in the past, but adapting and responding towards the rapid changes of business environments by taking the suitable approach depending on the conditions prevailing at that time to be leveraged in strategy formulation. The main objectives of this research were to propose a model of business strategy formulation that integrates Knowledge Management (KM), Competitive Intelligence (CI), and Strategic Leadership (SL) as leverage in the business strategy formulation (BSF), as well as establish the mediation effect of Strategic Leadership (SL). This research adopted a quantitative approach that fully utilized the survey method through an online platform for data collection. A questionnaire survey randomly distributed to 331 managers working at the local-owned MSC Status companies. All the collected data were analyzed using the SmartPLS software. The result of the study revealed that there was a direct effect of KM and CI on SL and BSF. Nevertheless, CI found to be the most crucial factor than KM for BSF, and KM is more critical than CI to improve SL. Meanwhile, SL indeed not only an indicator to BSF but also has mediating effect in the relationship between KM, CI and BSF. Overall, the findings of the research are meaningful to add new knowledge for the knowledge fields as well as a practical context to facilitate the strategy formulation.